Formation of a novel colored product during the Maillard reaction of D-glucose - Knerr, Thomas; Lerche, Holger; Pischetsrieder, Monika; Severin, Theodor (Journal of Agricultural and Food Chemistry, 2001)
Reactions between reducing sugars and proteins or amino acids (Maillard reaction) lead to the formation of yellow to brown products (melanoidins) that are important for food preparation and processing, such as baking, roasting, or malt production. Thus far, the structures of the melanoidins have not been elucidated, although some structural insights have been gained from model reactions. In this study, D-glucose was heated with an amine and two colored compounds were detected by HPLC/UV-vis. After purification, the main product was identified as [(4aS,6R,7S,8R,8aR)-4,-4a, 6,7,8,8a-hexahydro- 7,8-dihydroxy-6-hydroxymethyl- 1,4- dipropyl- 1H-pyrano [2,3 -b] pyrazine-2-yl] -1-hydroxy-3-buten-2-one (1a). For the minor compound (2a), some spectral data were obtained, but the structure was not fully characterized, 1a and 2a are the main colored compounds when the reaction is performed in alcoholic solution or on a cellulose surface. Thus, it was concluded that products with an analogous structure are important for the color formation of foodstuffs with low water activity.
UnivIS-Import:2015-03-09:Pub.2001.nat.dchph.llmch.determ_2
Keywords: [(4aS; 6R; 7S; 8R; 8aR)-4; 4a; 6; 7; 8; 8a-hexahydro- 7; 8-dihydroxy-6-hydroxymethyl-1; 4-dipropyl-1H-pyrano[2; 3-b]pyrazine-2- yl]-1-hydroxy-3-buten-2-one; Color formation; D-glucose; Maillard reaction; Melanoidins